2006
DOI: 10.1083/jcb.200602149
|View full text |Cite
|
Sign up to set email alerts
|

IKKβ programs to turn on the GADD45α–MKK4–JNK apoptotic cascade specifically via p50 NF-κB in arsenite response

Abstract: Cross talk between NF-κB and c-Jun N-terminal kinases (JNKs) has been implicated in the cell life and death decision under various stresses. Functional suppression of JNK activation by NF-κB has recently been proposed as a key cellular survival mechanism and contributes to cancer cells escaping from apoptosis. We provide a novel scenario of the proapoptotic role of IκB kinase β (IKKβ)–NF-κB, which can act as the activator of the JNK pathway through the induction of GADD45α for triggering MKK4/JNK activation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
132
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 85 publications
(140 citation statements)
references
References 44 publications
7
132
1
Order By: Relevance
“…SUMOylation of Nucleolin Increased gadd45␣ mRNA Stability-Growth arrest and DNA damage-inducible gene 45␣ (GADD45␣) is one of the mediators of arsenite-induced apoptosis, as we found previously (47,48); therefore, GADD45␣ induction was investigated to define its involvement in the biological function of SUMO-nucleolin. Consistent with inhibition of the apoptotic response, overexpression of Mn-SOD (Fig.…”
Section: Discovery Of Nucleolinmentioning
confidence: 99%
See 2 more Smart Citations
“…SUMOylation of Nucleolin Increased gadd45␣ mRNA Stability-Growth arrest and DNA damage-inducible gene 45␣ (GADD45␣) is one of the mediators of arsenite-induced apoptosis, as we found previously (47,48); therefore, GADD45␣ induction was investigated to define its involvement in the biological function of SUMO-nucleolin. Consistent with inhibition of the apoptotic response, overexpression of Mn-SOD (Fig.…”
Section: Discovery Of Nucleolinmentioning
confidence: 99%
“…In terms of nucleolin, we did observe a weak presence of nucleolin SUMOylation without any stimulation, which might account for its steady nuclear sequestration. Meanwhile, the protein SUMO level is dynamically regulated under various stress conditions, including osmotic stress, hypoxia, heat shock, and oxidative stress (36,37,48). On one hand, a low or moderate level of oxidative stress inhibits SUMOylation by oxidation of SUMO E1 and E2 enzymes, leading to disulfide bond formation between SAE1 and UBC9 (62).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inhibiting Ras activation by interacting with Grb2 might be another possible mechanism for AP-1 pathway repression by p27. In addition, our previous study demonstrated that through regulating GADD45/MKK4/JNK activation, the IB kinase/ NFB p50 pathway mediates the cellular apoptotic process upon arsenite exposure (10). The IB kinase/NFB p50/ GADD45/JNK pathway might be another possible linkage for p27 regulation of JNK/c-Jun-dependent Hsp27 and Hsp70 transcription.…”
mentioning
confidence: 99%
“…Arsenite occurs naturally in the earth's crust and is widely distributed in the environment. Our previous studies have demonstrated that arsenite exposure is able to initiate both cell apoptosis and cell transformation through different signaling pathways, dependent on dosages of arsenite exposure in various cell lines (7)(8)(9)(10)(11). In this study, we found, for the first time to our knowledge, that p27 mediated the suppression of Hsp27 and Hsp70 induction by arsenite through inhibiting JNK2/c-Jun-and HSF-1 (heat shock factor 1)-dependent transcriptional activation, which may provide novel molecular mechanisms underlying the tumor-suppressive function of p27 in the arsenite response.…”
mentioning
confidence: 99%